Pandangan Guru Terhadap Assesmen Nasional Berbasis Komputer Sebagai Sarana Evaluasi Sistem Pendidikan di Mi Muhammadiyah Karanganyar - Sartini, Sartini; Handayani, Andriani Condro Retno; Muhibbin, Muhibbin; Sumardi, Sumardi (Peneliti.net, 2024)
This study reviews teachers' views on the implementation of computer based national assessments as an instrument for evaluating the education sistem at MI Muhammadiyah Karanganyar. The aims of this research include analyzing teachers' views on the implementation of the National Assessment at MI Muhammadiyah Karanganyar, identifying the challenges encountered by teachers in implementing the Minimum Competency Assessment, character survey, and learning environment survey, as well as identifying the attempts done by teachers in order to implement the Minimum Competency Assessment, character survey, and learning environment surveys. The research method used is descriptive qualitative. Data was gathered through interviews and documentation. Data analysis was accomplished by reducing the data by summarizing interview results, presenting the informaition in narrative format, and inferred conclusions. The research outcomes show that teachers' views on national assessments tend to be positive, as reflected in their opinions. Obstacles in implementing the Minimum Competency Assessment and character survey include slow understanding and operation of IT by some students as well as limited infrastructure. Meanwhile, obstacles in implementing the learning environment survey include difficulties in understanding the form of questions in the instrument by some teachers. Attempts made by teachers to overcome these obstacles include joint efforts with schools to improve facilities and infrastructure, upskilling students in computer operation, getting used to daily literacy activities, and carrying out exercises in filling out learning environment surveys.